Life cycle and host preferences in the Agapanthus borer (Neuranethes spodopterodes) - Dabee, Vidushi Prema (Department of Biological Sciences, 2015)
The species Neuranethes spodopterodes is a pest of the Agapanthus species. The larva feeds gregariously on the leaves and rhizomes and cause extensive damage to the plant. This study shows the N.spodopterodes have 6 larval instars. The use of the head capsule width as a morphometric parameter and applying it to Dyar's rule gives significant results which allow for adequate determination of the larval instar. The Agapanthus borer has a life cycle that last approximately 84 days. Some species of Agapanthus are the preferred host plant for oviposition by the female N.spodopterodes. Agapanthus inapertus, Agapanthus caulescens and Agapanthus praecox are the most infested with the Agapanthus borer eggs. Leaf sizes do not appear to be a factor that influences the female choice. There appears to be no preference from the larva during feeding. The larva fed equally on all the six Agapanthus species including A. africanus (p>0.05). This shows that the chemical composition of these species is closely related. Since the larva has no feeding preference, this reinforces the fact that it is the female moth that chooses the host plant and that it abides with preference-performance hypothesis. Since A. africanus is subjected to feeding by the larva under laboratory conditions, it could potential imply that in the event of a range shift by the gravid female, that this species of plant is at risk of extinction. The presence of a parasitoid wasp, Trichogramma in the egg of N. spodopterodes and that the level of parasitism is about 86% suggests that this parasitoid could potentially be used as a biological control agent of the Agapanthus borer.